Biomarkers in drug discovery and development : a handbook of practice, application, and strategy - Rahbari, Ramin, 1965-; Van Niewaal, Jonathan, 1979-; Bleavins, Michael R. (John Wiley & Sons, Inc., 2020)
"This book continues the legacy of a well-established reference within the pharmaceutical industry -- providing perspective, covering recent developments in technologies that have enabled the expanded use of biomarkers, and discussing biomarker characterization and validation and applications throughout drug discovery and development. Several case studies of biomarkers that have helped and hindered decision making are presented, as well as an overview of the areas where proper use of biomarkers can substantively impact timelines and costs by streamlining development programs, enabling selection of better compounds and reducing late stage attrition, and facilitating personalized medicine. The new edition updates existing information with developments in pre-clinical and clinical testing and introduces substantial new materials on data mining, decision making, and personal genetic tools. With such significant expansion and revision, the 2nd edition ensures Biomarkers in Drug Development remains a key resource for biotechnology and major pharmaceutical companies, and their efforts to improve and expedite drug development"--